Determination of UV-Vis Spectrophotometry with Differential pH on Total Anthocyanin Levels of Ethanol Extract of Cordyline fruticosa (L.) A. Cheval Leaves - Yuri Pratiwi Utami; Ainun Jariah; Rahmah Mustarin (Pharmaceutical Reports, 2023)
Cordyline fruticosa (L.) A. Cheval is a traditional medicinal plant contains several chemical compounds including saponins, tannins, flavonoids, polyphenols, steroids, and anthocyanins. The purpose of this study was to determine the total anthocyanin levels of red andong leaf extract. In this study, red andong leaf was extracted using the maceration method with 70% ethanol solvent. Furthermore, qualitative testing was carried out by screening the phytochemicals of red andong leaf extract and continued with qualitative-specific testing for anthocyanins. Then the anthocyanin levels were measured using UV-Vis spectrophotometry with differential pH. The results showed that anthocyanins were of cyanidin type. Furthermore, the measurement of total anthocyanin levels was carried out using the differential pH method. Based on these results it can be concluded that the totalanthocyanin levels of andong red leaf extract (Cordyline fruticosa (L.) A. Cheval) 17.76mg/L.